Geometry Representation Abilities: What is The Impact of Using The 6E-Instructional Model Integrated with Augmented Reality? - Sudirman Sudirman; Ardi Dwi Susandi (Universitas Sebelas Maret, 2024)
This research aims to analyze the impact of the 6E-Instructional Model Integrated Augmented Reality in improving students' 3D geometric representation abilities. A type of quasi-experimental design, one group pretest-posttest, is used for objective research of answers. The subjects of this research were 8th-grade students at a private school in Indramayu Regency, Indonesia, totaling 288 students divided into eight classes. Based on this number, one class of class VIII B was selected as the research sample. Furthermore, the research instrument uses a geometric representation ability test. In addition, the data obtained from the test results were analyzed using the paired sample t-test. The research concluded that AR technology can be integrated into constructivist learning, including 6E Instructional Mode. Furthermore, based on the paired sample t-test, it was concluded that using 6E-IM integrated AR increased the 3D geometric representation abilities of class VIII students in one of the private schools in the Indramayu Regency. Therefore, this research provides a foundation for advanced learning in mathematics, especially regarding integrated technology and learning models.